In Vitro Comparison of Flexural Strength of a Bioactive Composite and a Reinforced Hybrid Glass Ionomer - Keyvan Saati; Sara Valizadeh; Marjan Ayyari; Shahram Amirifar (Frontiers in Dentistry)
Objectives: The present study was conducted to compare the flexural strength of a bioactive composite and a reinforced hybrid glass ionomer (GI).